2006
DOI: 10.1002/adma.200501611
|View full text |Cite
|
Sign up to set email alerts
|

Testing Carbon‐Coated VOx Prepared via Reaction under Autogenic Pressure at Elevated Temperature as Li‐Insertion Materials

Abstract: V 2 O 3 powder is frequently used in conductive polymer composites and in catalysts. [1][2][3] In addition, a variety of VO x and MVO x (e.g., V 2 O 5 , V 6 O 13 , CaV 3 O 7 ) compounds have been suggested and tested as cathode materials for rechargeable Li batteries. [4][5][6][7][8][9][10] These vanadium oxide-based compounds are still among the most intensively studied cathode materials for rechargeable Li batteries. It should be noted that studies related to Li-battery materials are of high interest in mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 31 publications
2
95
0
3
Order By: Relevance
“…This rate capability is higher than those of carbon-coated V 2 O 5 and other V 2 O 5 -based electrodes. [13,15,17] The experi- mental results obtained show that the mixed-conducting nanostructure favorably reduces the diffusion length for lithium ions and enables the high rate performance of lithium-based batteries. In summary, an optimized nanostructured electrode design has been proposed.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This rate capability is higher than those of carbon-coated V 2 O 5 and other V 2 O 5 -based electrodes. [13,15,17] The experi- mental results obtained show that the mixed-conducting nanostructure favorably reduces the diffusion length for lithium ions and enables the high rate performance of lithium-based batteries. In summary, an optimized nanostructured electrode design has been proposed.…”
mentioning
confidence: 88%
“…[26] The third plateau at 2.3 V can be ascribed to a further lithium insertion into LiV 2 O 5 , which is also highly reversible [Eq. (3)], [5,13] LiV…”
mentioning
confidence: 99%
“…Figure 3(c) represents a typical Raman spectrum of a-CNTs, which is characteristic for amorphous carbon because of the presence of the D-(1348 cm -1 ) and G-bands (1595 cm -1 ) (Ilie et al 2002; Odani et al 2006). It was reported that the D-band (1348 cm -1 ) is usually associated with the vibrations of carbon atoms with dangling bonds for the in-plane terminations of disordered graphite, and the G-band (corresponding to the E 2g mode) is closely related to the vibration in all sp 2 -bonded carbon atoms in a two-dimensional hexagonal lattice, such as in a graphitic layer, corresponding to the E 2g mode (Dresselhaus et al 1999;llie et al 2002;Odani et al 2006;Sun et al 2006;Zhang et al 2012d,e). These two peaks are broad in figure 3(c), indicating that the carbon in the as-prepared a-CNTs is of poor crystallinity, corresponding to the previous report (Sun and Li 2004;Zhang et al 2011bZhang et al , 2012b.…”
Section: Resultsmentioning
confidence: 98%
“…The high theoretical capacities of V 2 O 5 are especially attractive, for example, 294 mA h g −1 for two lithium insertion/extractions at 4.0 − 2.0 V. Despite these advantages, V 2 O 5 has a low intrinsic electrical conductivity (10 −2 to 10 −3 S cm −1 ) and sluggish lithium-ion diffusion (∼10 −12 cm 2 s −1 ), leading to poor capacity retention and rate capabilities [11][12][13][14]. In addition, phase transformations of Li x V 2 O 5 during repeated charge/discharge processes (e.g., ␣ phase for x < 0.1, phase for 0.35 < x < 0.7, ␦ phase for x = 1, ␥ phase for 1 < x < 3, and phase for x = 3) often cause structural instabilities, and they degrade the cycling performances [15][16][17]. These drawbacks have hampered the practical applications of this cathode material in commercial LIBs.…”
Section: Introductionmentioning
confidence: 98%